Análisis del Proceso de Producción de Bebida Alcohólica Fermentada a Base de Miel Monofloral y Multifloral - Puga Lascano, Sonnia Alexandra (2024)
Mead is one of the oldest alcoholic beverages in the world, which is the result of the fermentation of alcohol with water and yeast, appeared about 700 years ago in civilizations as diverse as India, China, Egypt, Iran and Persia, at the time it was called the nectar of the gods. The methodology used was a bibliographic review. Modern brewing processes, which use selected yeasts in controlled environments, offer greater control over fermentation, which translates into greater consistency in flavor and quality of the final product. Saccharomyces cerevisiae yeast stands out for its efficiency in fermentation, ensuring optimal results. Monofloral honeys, such as thyme, acacia and lavender, are appreciated for their unique flavor and aroma, ideal for mead production. On the other hand, multifloral honeys, such as wildflower and forest honeys, offer greater availability and are more accessible for large-scale production. In conclusion, the modern method with selected yeasts and the use of monofloral honeys offer the ideal combination to obtain a high quality and consistent mead.